A Role of Plasminogen in Atherosclerosis and Restenosis Models in Mice - Plow, Edward F.; Ploplis, Victoria A.; Busuttil, Steven; Carmeliet, Peter; Collen, Desire (Thrombosis and Haemostasis, 1999)
In addition to its preeminent role in fibrinolysis, the plasminogen system is believed to play a key role in mediating cell migration. Leukocyte migration into the vessel wall is a key and early event in the development of the lesions of atherosclerosis and restenosis, pathologies which may be viewed as specific examples of vascular inflammatory responses. The development of mice in which the plasminogen gene has been inactivated affords an opportunity to test the contribution of plasminogen in leukocyte migration during in vivo. This article summarizes recent studies conducted in murine models of the inflammatory repsonse, restenosis and atherosclerosis in which leukocyte migration, and in particular monocyte/macrophage migration, has been evaluated in plasminogen-deficient mice. Recruitment of these cells through the vessel wall in inflammatory response models and into the vessel wall in restenosis and transplant atherosclerosis models is substantially blunted. These data implicate plasminogen in the migration of leukocytes in these murine models. With the numerous correlations between components and/or activation of the plasminogen system in restenosis and atherosclerosis, these results also support a role of plasminogen in the corresponding human pathologies.
Keywords: Leukocytes; macrophages; smooth muscle cells; inflammation